The utilization and extinction of Juniper trees from the Negev desert (Israel) - Data from a late 6th–5th millennia site of Har Harif. (March 2023) - Vardi, J.; Yegorov, D.; Degen-Eisenberg, D.; Boaretto, E.; Langgut, D.; Avni, Y.; Caracuta, V.
Abstract: The excavation of Har Harif 45, a campsite radiometrically dated to the 6th–5th millennia BCE, in the Negev highlands (Israel) uncovered many charcoals determined as Phoenician juniper ( Juniperus phoenicea ). Today, Phoenician juniper is absent from the Negev desert and can only be found on the ridges of northern Sinai (Egypt) and Jordan. Based on the relative abundance of polished stone axes and adzes found in Har Harif 45 in comparison to other contemporaneous sites, we suggest that the extinction of juniper trees from the Negev highlands was caused mainly by intensive and selective cutting of this highly beneficial woody species. On a wider view, the disappearance of Juniperus phoenicea from the Negev Desert provides a good example of human impact on the natural environment during the transition from hunter-gather societies to late Pottery Neolithic (and later periods of the 6th–5th millennia BC) pastoralist societies, where a greater population density increased the demand for natural resources such as juniper wood. We show that the archaeological evidence from Har Harif 45 combined with the archaeobotanical data sheds new light on the human influence on the Negev highland environment during the late 6th and 5th millennia BC. Highlights: Juniper trees ( Juniperus phoenicea ) does not grow in the Negev highlands, Israel. Mediterranean maquis with Junipers existed in the Negev during late prehistory. Polished bifacial tool used for tree felling were found. Tree felling was conducted in the Negev highlands in late prehistory. The agent behind the extirpation of the Juniper trees relates to human pressure.